The Effect of Alkali Addition and Coating Time on Hydrophilic Properties of Antimocrobial Ceramic Tiles - Irna Rosmayanti; Rizky Berliana Wijayanti; Eneng Maryani (Balai Besar Keramik, 2019)
Antimicrobial glaze is used for sanitation needs in special environments such as hospitals or schools. Antimicrobial properties of TiO2 involve photocatalytic activity on inorganic material. A hydrophilic surface, with contact angle value <65o, is resulted by those activity. In this study, polished tile coating was done using TiO2 material which had been prepared through a dissolving process in sulfuric acid followed by gel formation with addition of 2 types of alkali, ammonia and ammonium bicarbonate. The TiO2 gel formed was dispersed in aquadest and then coated on the surface of the tile by dip coating with various deposition time (3 hours, 6 hours and 53 hours). ANOVA test results represent that both main effect of alkali type and coating time, and interaction effect of these variable produce significant effects on contact angles. Addition of ammonium bicarbonate produce better hydrophilic surface on the tile than addition of ammonia. The longer coating time will increase hydrophilic characteristic of the surface.